Current state of vaccine development and targeted therapies for COVID-19: Impact of basic science discoveries (2020)
Coronavirus disease-19 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). SARS-CoV-2 is closely related to two other coronaviruses that caused disease epidemic breakouts in humans in the last 2 decades, namely, severe acute respiratory distress syndrome coronavirus (SARS-CoV) and Middle East Respiratory Syndrome coronavirus (MERS-CoV). The similarities have enabled the scientists to apply the basic scientific discoveries garnered from studying the structure and modus operandi of SARS-CoV and MERS-CoV to develop therapies that specifically target SARS-CoV-2 and to develop vaccines to prevent COVID-19. Targeted therapies, including the use of antibodies to prevent virus entry, nucleotide analogues to prevent viral replication, and inhibitors of proteases to prevent virion formation, among others, are being tested for their clinical efficacy. Likewise, complete sequencing of the SARS-CoV-2 and identification of its structural and non-structural proteins have enabled development of RNA-, DNA-, and peptide -based vaccines as well attenuated viral vaccines to instigate the host immune responses. The clinical impacts of the basic science discoveries are amply evident on the rapid pace of progress in developing specific anti-viral therapies and vaccines against SARS-CoV-2. The progress emphasizes the merit of discovering the fundamental scientific elements, regardless of whether or not they have apparent or immediate clinical applications.